PENGARUH MANAJEMEN ASET, MANAJEMEN LIABILITI, MANAJEMEN ASET LIABILITI TERHADAP ECONOMIC VALUE ADDED (EVA) PADA PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hamidah Hamidah; Ika Nur Setiowati; Agung Dharmawan Buchdadi (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
ABSTRACTGenerally, company wants to optimize its profit. Properly manage the asset management, liability management and asset liability management can provide value added profits for the company. A sample of research consists of 18 banking companies listed at Indonesia Stock Exchange (IDX) during the 2005-2009. This research investigate the relationship net loans/total earning assets (NLA), non performing loan (NPL), liabilities/total assets (LA), equity/total assets (EA), net interest margin (NIM), loan to deposite ratio (LDR) on economic value added (EVA). The research use regression of panel data. The result show that net loans/total earning assets (NLA), liabilities/total assets (LA), equity/total assets (EA), net interest margin (NIM), loan to deposite ratio (LDR) are have significant effect on economic value added (EVA) but non performing loan (NPL).Key words: NLA, NPL, LA, EA, NIM, LDR, EVA